Tool wear and surface roughness of Al2O3 particle-reinforced aluminium alloy composites - Sahin, Y; Kok, M; Celik, H (Elsevier Science Sa, 2002)
The machinability of 2024 aluminium alloy reinforced with Al2O3 particles using varying size and weight fraction of particles up to 30 wt.% by a vortex method was carried out at different cutting conditions. Experiments were carried out with TiN (K10) coated carbide tools and TP30 coated carbide tools at various cutting speeds. Tool wear and surface roughness in the turning of Al2O3 particle-reinforced aluminium alloy composite was investigated with special attention paid to the effects of material structures. The experimental results showed that tool life increased with increasing the cutting speed for both cutting tools and the tool life of TiN (K10) tool was significantly longer than that of TP30 tool. It is observed that the major wear form of the tools are the combination of rounding of nose and flank wear in addition to removal of coated layer from the substrate for the TiN (K10) tool but edge chipping and rounding of nose was evident for the TP30 tool. Moreover, the optimum surface roughness was obtained at a speed of 160 m min(-1) while the maximum surface roughness value was found in the machining of the 10% Al2O3 composites with particle size of 16 mum. The surface roughness also increased with the increasing weight percentage of the particles. Furthermore, physical appearance of chips produced by TiN (K10) cutting tools were discontinuous and smaller sizes while the appearance of chips produced by TP30 cutting tools were continuous type and larger size. (C) 2002 Elsevier Science B.V. All rights reserved.
Keywords: Al2O3; composites; coated tools; wear; tool life; roughness